Number of samples, replication and measurements for a screening technique of sorghum emergence potential in crusted soils - Mason, S.C.=700 1 Lasa, J.M.; Eskridge, K.M.
(Es, En)
ilus., 11 ref.
Keywords: SORGOS; EMERGENCIA; SUELOS AGRICOLAS; COSTRA DEL SUELO; ESPAÑA; NASCENCIA; TAMAÑO DE MUESTRA; REPETICION